BIOSENSOR FOR THIAMINE DETECTION USING YEAST SACCHAROMYCES CEREVISIAE - Leonardus Riski Nainggolan; Siti Rahmawati Ibmar; Sumi Komala; Vira Annisa Rosandi; Lazuardi Umar (Prodi Fisika FST UNJA, 2022)
Nowadays, people's lifestyles have undergone significant changes, such as decreased physical activity and increased sedentary behavior, as well as an increase in nutritionally unbalanced diets, especially in vitamin B1 (thiamine) intake. Deficiency and excess of thiamine can cause various diseases. Based on this, it is important to know the level of thiamine intake in dietary supplements and medicines. This study used a biosensor with amperometric principles to determine the effect of thiamine on the yeast Saccharomyces cerevisiae as a cell model. Measurements were made by adding controlled vitamins to cell metabolic activity using an amperometric biosensor based on Pt/Ag electrodes. An amperometric biosensor will measure the current from a reduction and oxidation reaction with a constant potential. The effect of adding vitamins to yeast cells was observed in the form of cellular respiration, which was expressed as a parameter of dissolved oxygen level (DO). Vitamins used as samples were given various concentrations of 30 mM, 45 mM, and 60 mM. The addition of thiamine causes an increase in the potential value for each increase in concentration, indicating that DO levels in the cell environment have decreased due to yeast cells consuming O2 during the respiration process. The results of this study indicate that yeast cell-based biosensors can detect variations in the concentration of thiamine for further health applications.